IMPLEMENTASI PENGADAAN RAMAH LINGKUNGAN PADA PROGRAM MAKAN BERGIZI GRATIS SESUAI DENGAN PERATURAN PRESIDEN NOMOR 46 TAHUN 2025 TENTANG PENGADAAN BARANG/JASA PEMERINTAH - Komala Sari (Smart Education, 2026)
Abstract: The Government has transformed procurement from an administrative task into a tool for sustainable development that balances economic, social, and environmental dimensions. The Free Nutritious Meals (MBG) Program, as a strategic national policy, requires a procurement system that not only ensures the availability of nutritious food but also food commodities, supporting services, food processing, distribution, and the management of food residues and waste on a large scale This study aims to analyze the implementation of green procurement in the MBG Program based on Presidential Regulation Number 46 of 2025 concerning Government Procurement of Goods and Services, identify the challenges in its implementation, and formulate strategies for policy optimization. This research employs a normative legal research (doctrinal legal research) method using statutory, conceptual, and analytical approaches. The findings indicate that the application of Green Procurement principles in the MBG Program can be realized through the procurement of locally sourced food, efficient distribution systems, the use of environmentally friendly packaging, waste reduction initiatives, and strengthened supplier governance. The main challenges include the limited availability of green suppliers, inadequate human resource capacity, and insufficient monitoring systems. Policy optimization requires the digitalization of green procurement, the strengthening of technical regulations, and enhanced multi-stakeholder collaboration. Keywords: Green Procurement; Free Nutritious Meals; Presidential Regulation Number 46 of 2025 Abstrak: Perubahan paradigma pengadaan barang/jasa pemerintah (PBJP) mulai terjadi dari pendekatan administratif sampai dengan instrumen pembangunan berkelanjutan yang mengintegrasikan aspek ekonomi, sosial, dan lingkungan. Program Makan Bergizi Gratis (MBG) merupakan program nasional yang melibatkan pengadaan bahan pangan, jasa pendukung, pengolahan, distribusi, serta pengelolaan sisa pangan dan limbah dalam skala besar. Besarnya rantai pasok tersebut menjadikan pengadaan sebagai instrumen strategis untuk menerapkan prinsip ramah lingkungan. Penelitian ini bertujuan menganalisis implementasi pengadaan ramah lingkungan pada Program MBG berdasarkan Peraturan Presiden Nomor 46 Tahun 2025 tentang Pengadaan Barang/Jasa Pemerintah, mengidentifikasi tantangan pelaksanaannya, serta merumuskan strategi optimalisasi kebijakan. Metode peneliuttian menggunakan penelitian hukum normatif (doctrinal legal research) dengan pendekatan peraturan perundang-undangan (statute approach), konseptual (conceptual approach), dan analitis (analytical approach). Hasil penelitian menunjukkan bahwa penerapan prinsip Green Procurement dalam MBG dapat diwujudkan melalui pengadaan pangan lokal, efisiensi distribusi, penggunaan kemasan ramah lingkungan, pengurangan limbah, serta penguatan tata kelola penyedia. Tantangan utama meliputi keterbatasan penyedia hijau, kapasitas sumber daya manusia, dan sistem monitoring. Optimalisasi diperlukan melalui digitalisasi pengadaan hijau, penguatan regulasi teknis, serta kolaborasi multipihak. Kata kunci: Pengadaan Ramah Lingkungan; Makan Bergizi Gratis; Perpres 46 Tahun 2025.